Rural Banking Dynamics: Assessing the Correlation Between Employee Work Performance and Financial Performance - Berbano, Jaime; Castrana, Lovella; Pisueña, Jay Jay (Journal of Interdisciplinary Perspectives, 2025)
This study evaluates the relationship between employee work performance and financial performance in a rural bank in Iloilo City. The research aims to determine whether employee performance influences the bank’s financial strength. Primary data was collected using a structured questionnaire to assess task and contextual performance among all bank employees. Secondary data was analyzed using the CAMELS model, which evaluates financial health based on Capital Adequacy, Asset Quality, Management Efficiency, Earning Quality, Liquidity, and Sensitivity. A descriptive-relational analysis was conducted, with responses measured using a 5-point Likert scale. Results indicate that both task and contextual performance were rated moderately. The bank's financial performance was assessed as moderate to low over the past three years, with critical weaknesses in Return on Equity (ROE), Capital to Assets (CATA), asset quality, and management efficiency. Statistical analysis found no significant relationship between employee performance and financial performance. These findings suggest that other factors may have a stronger impact on the bank’s financial health, highlighting the need for further investigation into external influences and operational strategies.